2015
DOI: 10.4088/pcc.14m01728
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a US Food and Drug Administration Drug Safety Communication on Zolpidem Dosing

Abstract: The release of a drug safety communication by the FDA resulted in a statistically significant increase in proper dosing of zolpidem in women. Further research is needed in order to determine the impact of FDA alerts on prescribing patterns and the reasons for therapeutic substitution after such alerts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 4 publications
2
6
0
Order By: Relevance
“…The resulting mixture was placed in a freezer (at −14 • C) overnight, and the next day, 3 mL of diethyl ether was added, and the precipitate was washed with a small amount of diethyl ether (2 mL) to give I with 73% of yield (90 mg). The spectral data matched those previously reported [36]; white solid, mp 195-197 • C; 1 Sample preparation for microscope imagining: 1mg of zolpidem tartrate I was placed on a microscope plate, dissolved in a drop of methanol and evaporated directly on the microscope plate. The images were taken immediately after the solvent was evaporated using polarized light microscope Hund Wetzlar type H600/12 (Helmut Hund GmbH, Wetzlar, Germany).…”
Section: General Methodssupporting
confidence: 79%
See 2 more Smart Citations
“…The resulting mixture was placed in a freezer (at −14 • C) overnight, and the next day, 3 mL of diethyl ether was added, and the precipitate was washed with a small amount of diethyl ether (2 mL) to give I with 73% of yield (90 mg). The spectral data matched those previously reported [36]; white solid, mp 195-197 • C; 1 Sample preparation for microscope imagining: 1mg of zolpidem tartrate I was placed on a microscope plate, dissolved in a drop of methanol and evaporated directly on the microscope plate. The images were taken immediately after the solvent was evaporated using polarized light microscope Hund Wetzlar type H600/12 (Helmut Hund GmbH, Wetzlar, Germany).…”
Section: General Methodssupporting
confidence: 79%
“…Zolpidem 1 is one of the most widely prescribed hypnotic medications in the United States, with an annual prescription rate of nearly 39 million [1,2]. It was developed in the late 1980s [3] and 1990s as a subtle alternative to benzodiazepines, which could rapidly promote sleep, while retaining the negligible risk of impaired daily functioning [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We are aware that patients treated with benzodiazepine receptor agonists could be treated with benzodiazepines, and believe our findings with benzodiazepine hypnotics also apply to benzodiazepine receptor agonists registered as hypnotics such as zolpidem. The SAMHSA reported that the visits to emergency departments due to overmedication with zolpidem doubled from 2005-2006 to 2009-2010 in the USA [46] , leading to a warning from the US Food and Drug Administration to decrease the recommended dose by 50% in women [52] .…”
Section: Discussionmentioning
confidence: 99%
“…Although the FDA now recommends dosing women with only 5 mg or 6.25 mg of zolpidem, at least to begin with, only 5% of women and 10% of elderly were prescribed these low doses in 2012 153 . Apparently, there was little change in dosing for women and elderly after the FDA recommended the low doses in 2013 153 , 156 . Moreover, 23% of patients with sustained use took another drug targeting the same receptors.…”
Section: Contributory Factors Combined With Hypnotics Could Cause Covmentioning
confidence: 99%